Gaya Hidup Ngopi Sebagai Perilaku Konsumsi - Profil Yugantara; Rachmad K. Dwi Susilo; Sulismadi Sulismadi (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
So many coffee shop in Malang have recently been able to create a new lifestyle for some people who we usually hear about ngopi. Ngopi activities are not necessarily limited to drinking coffee and so on, but there are activities of consumsing symbols that can provide messages or signs for individuals who consume them and other people who see them. This study aims to describe the ngopi lifestyle as a consumption behavior in the people of Malang City. This research method uses descriptive qualitative with the technique of determining the research subject using accidental sampling. Based on the result of the research that ngopi is currently an icon of modern lifestyle and in the ngopi lifestyle there are consumption behaviors that aim to gain prestige, images, social status and consciously or unconsciously that will differentiate individuals from others. Starting from a public capture of simulations made by brands, it is able to distort our minds that is not real becomes real. That way, raises a distinction or process of classifying the tastes of individuals or groups, in a grouping of taste in which there are classifications in an individual or group.